Attachment styles among Malaysian trainee teachers: how it mediates the relationship between self efficacy with professionalism. a study using AMOS (SEM) Model - Muhamad Suhaimi Taat; Roslee Talip; Abd Said Ambotang (Universiti Malaysia Sabah, 2012)
The main purpose of this research was to investigate the influence of attachment style and self-efcacy on professionalism among trainee teachers in teacher training institutes (IPTA and IPG) in Sabah. It will also try to identify the mediation function of the attachment style between the independent with the dependent variables. his quantitative survey research involved 295 students from first year to the final year (161 from IPTA and 134 from IPG) using purposive, cluster and simple random samplings. This research used four types of Attachment Style developed by Bartholomew and Horowitz (1991), and Teachers Efficacy instrument from Conceptual Classroom Management by Friedman & Kass (2002) as the main platform for the research framework. Data was analysed using SPSS Version 21 and AMOS Version 21. Descriptive and inferential statistics were used to interpret and explain the data. The ma/n finding demonstrated significant influence of independence variables which are Preoccupied attachment style and self-efficacy on the dependence variable which is professionalism. The multiple regression analysis showed that efficacy was the major influence on the trainee teachers professionalism (, ß = 0.504, R2= 0.304, p=0.001). Moreover, path analysis of structural equation model (SEM) also showed that the regression model established fit with the data collected. Therefore, proved both two independence variables mentioned above were directly and indirectly correlated with the dependence variable. The Pearson correlation result showed that there was significant positive correlation among the variables involved. The independent samples t-test indicated that there was no significant difference between mean score of the dependent variable in relation of gender. The findings also showed there was no significant difference between mean score of dependent variable in relation of institutes (IPTA & IPG). It is hoped this research will be able to contribute valuable input for the enhancement of the national educational system.